# Algebra help

posted by .

Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3.

• Algebra help -

For f(of)g(x), take (2x+3) - (2x+3)^2
(insert g(x) where the "x" is in f(x) )

For g(of)f(x), take 2[x-x^2] +3

## Similar Questions

1. ### Algebra 2

If f(x) = x-3 g(x) = 2x+5 find fog and gof
2. ### Algebra

When Let f (x) = x^2 – 3x + 8 and g(x) = x – 5 Find Find the composite function of (fºg)(x) and simplify Find (fºg)(2) Find the composite function (gºf)(x)
3. ### Composite Functions

f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7) Find: (fog)(x) (gof)(x) (fog)(-1)
4. ### Math

Find (fog)(2) and (gof)(-2) f(x)=Square root of 4-x; g(x)=1-3x^2 Show work.
5. ### math

Find a. fog b. gof c. fof d. gog f(x)=4-x g(x)=3x-5
6. ### math

Find a. fog b. gof c. fof d. gog for each function f(x)=4-x g(x)=3x-5
7. ### college algebra

1. answer the following for the given quadratic function f(x)=x^2+10x-11 a.what is the vertex (h,k) of f?
8. ### Algebra

If f(x)= ln x, g(x) = e^3x, and h(x) = x^7, find the following... a) (fog)(x) What is the domain of fog?
9. ### Maths

Let f(x)= 2x+1 and g(x) = 3x^2-4 find: a) f^-1 b) gof (-2) c) fog (x)
10. ### College Algebra

For fx=6x-5 and gx=3x^2-4 find the following (fog)(x) Having problems understanding (gof(x)=g(f(x))= 3(f(x))^2-4 3(6x-5)^2-4 (36x-9-25)-4

More Similar Questions